Land application of adit water on historic mine tailings at Stillwater Mine - Teegarden, Travis P., author; Gilbert, Bruce E., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
Land application disposal (LAD) systems have been used throughout the U.S. for several decades, but land application of wastewater in Montana has little documentation. More importantly is the lack of literature on the performance of LAD systems. As companies and municipalities, both public and private, plan for future expansion, wastewater treatment and disposal issues are of significant concern. The State of Montana's "non-degradation" rule places strictly regulated limitations on the discharge of wastewater into Montana's public waters. These regulations have many entities seeking new technological methods and economical solutions for wastewater treatment and disposal that meet current standards. Stillwater Mining Company (SMC) has upgraded LAD systems and developed a water quality monitoring plan to stabilize and reclaim approximately 42 acres (17 hectares) of partially reclaimed chromium tailings. Forage on the LAD area supports resident mule deer and serves as winter range for bighorn sheep. In 1993, SMC commissioned MSE-HKM, Inc. (formerly HKM Associates) to design a new LAD system and monitoring program for the partially reclaimed tailings site. After two years of operation and monitoring, results show high levels of nitrogen utilization and significant forage improvement on the LAD site. The design considerations, operation, monitoring, and results of two years of land application at SMC are presented. Wildlife ecosystem and habitat enhancements have been achieved by increasing natural food sources and cover. Results show that land application disposal systems can be utilized to improve reclamation efforts and can economically provide treatment and disposal solutions to improve water quality.
1996 USCID wetlands seminar
Not digitized by CSUL Digital Services.
Presented at Water for agriculture and wildlife and the environment: win-win opportunities: proceedings from the USCID wetlands seminar on June 27-29, 1996 in Bismarck, North Dakota.